Preparation of Wound Healing Hydrogels Based on Silicon, Iron, Zinc, and Boron Glycerolates: Toxicological Profile, Hemostatic and Antimicrobial Effects - Tat’yana Khonina; Semyon Alekseenko; Elena Shadrina; Il’ya Ganebnykh; Alexander Mekhaev; Leonid Larionov; Maria Dobrinskaya; Nadezhda Izmozherova; Irina Antropova; Maxim Karabanalov; et al. (Pharmaceutical Science: New Insights and Developments Vol. 5, 2025)
Treating wounds and their rapid healing is considered an important topic in ancient and modern research. The use of hydrogels is a promising strategy for achieving hemostasis and wound healing. Sol-gel synthesis is one of the methods for obtaining hydrogels. An innovative direction in sol-gel synthesis is the use of biogenic element polyolates (glycerolates) as biocompatible precursors with a wide range of pharmacological activity. It was shown that hydrogels based on silicon, iron, zinc, and boron glycerolates are non-toxic, and exhibit pronounced hemostatic activity, as well as antimicrobial activity, which is more pronounced for silicon-iron-zinc-boron and silicon-iron-boron glycerolate hydrogels. The results obtained indicate that these glycerolate hydrogels are potential hemostatic and antibiotic-independent antimicrobial agents for topical wound healing applications in medical and veterinary practice.